Evaluation of the Knowledge, Attitudes and Practice of Veterinary Professionals and Senior Animal Health Students in Central Gondar Zone, Gondar, Ethiopia: Antimicrobial Use and Resistance Perspectives - Abibo Wondie Mekonen; Yesuneh Tefera Mekasha; Melaku Getahun Feleke; Atsede Getaneh; Meron Dereje; Misganew Bafe; Sete Nigussie; Achenef Melaku Beyene (Veterinary Medicine and Science)
ABSTRACT Background Antimicrobial resistance (AMR) poses a worldwide challenge to the well‐being of animals and humans. The emergence of AMR is largely attributed to the improper utilization and overuse of antimicrobials. In order to combat this issue and promote responsible antimicrobial use (AMU), it is imperative for veterinary professionals and graduating students to possess extensive knowledge, maintain positive attitudes, and adhere to good practices regarding AMU and AMR. Objective To assess the knowledge, attitude and practices (KAPs) of veterinary professionals and senior animal health students’ towards veterinary AMU and AMR. Methods A cross‐sectional study design was conducted on purposefully selected 200 participants (60 of them were veterinary professionals from the districts and towns, and the remaining 140 were senior animal health university students). A self‐administered, structured questionnaire was used to collect the necessary data, and descriptive statistics were used to summarize the data. Results The study revealed that, overall, study participants’ KAP were not satisfactory. From veterinary professionals, about 56.7% of respondents scored average knowledge, whereas 66.7% and 61.66% of them had negative attitudes and poor practices, respectively, on AMU and AMR. The study found that 56% of the participants’ think the previous knowledge they acquired regarding AMU and AMR was not sufficient, and the internet was used as a source of drug information by the majority of participants. The majority (72%) of them were not taking special training on AMU and AMR. Regarding senior animal health students, this study indicated that 52% and 69.2% of the respondents had poor knowledge and a negative attitude, respectively, towards AMU and AMR. Conclusion Overall, veterinary professionals in the central Gondar zone have average knowledge, a negative attitude and poor practices. Poor knowledge and a negative attitude were also observed among senior animal health students towards AMU and AMR. Therefore, to fill the observed gaps, activities that enhance the skills of veterinary professionals and students should be implemented. Ingreted measures with animicrobial stewardship program and Nationwide studies are highly suggested to evaluate the overall status of veterinary professionals towards AMU and AMR.